A general analysis of Wtb anomalous couplings*Supported by National Science Foundation of China (11275009, 11675002, 11635001), National Science Foundation (PHY-1315983, PHY-1316033) and DOE (DE- SC0011095). (June 2017) - Cao 曹, Qing-Hong 庆宏; Yan 岩, Bin 斌; Yu 于, Jiang-Hao 江浩; Zhang 张, Chen 宸
Abstract: We investigate new physics effects on the Wtb effective couplings in a model-independent framework. The new physics effects can be parametrized by four independent couplings, , , and . We further introduce a set of parameters x 0, x m, x p and x 5 which exhibit a linear relation to the single top production cross sections. Using recent data for the t -channel single top production cross section σ t, tW associated production cross section σ tW, s -channel single top production cross section σ s, and W-helicity fractions F 0, F L and F R collected at the 8 TeV LHC and Tevatron, we perform a global fit to impose constraints on the top quark effective couplings. Our global fitting results show that the top quark effective couplings are strongly correlated. We show that (i) improving the measurements of σ t and σ tW is important in constraining the correlation of (, ) and (, ); (ii) and are anti-correlated, and are sensitive to all the four experiments; (iii) and are also anti-correlated, and are sensitive to the F 0 and F L measurements; (iv) the correlation between and is sensitive to the precision of the σ t, σ tW and F 0 measurements. The effective Wtb couplings are studied in three kinds of new physics models: the G (221) = SU (2)1 ⊗ SU (2)2 ⊗ U (1) X models, the vector-like quark models and the Littlest Higgs model with and without T -parity. We show that the Wtb couplings in the left-right model and the un-unified model are sensitive to the ratio of gauge couplings when the new heavy gauge boson's mass ( M W′ ) is less than several hundred GeV, but the constraint is loose if M W′ > 1 TeV. Furthermore, the Wtb couplings in vector-like quark models and the Littlest Higgs models are sensitive to the mixing angles of new heavy particles and SM particles.